Terminalia arjuna Bark Extract Reduces High Fat Diet Induced Cardiac Damage in Wistar Rats by Altering Biochemical and Histological Parameters - Palanivelu, Priya; Jagadesan, Vijayakumar; Vijayaraghavan, Rajagopalan; Parthiban, Praveenkumar; Swaminathan, Madhankumar; Sivanesan, Senthilkumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Objectives: The aim of the present study was to examinethe protective effect of bark extract of TA (Terminalia arjuna) on HFD (high fat diet) induced biochemical and histopathological changes in Wistar rats. Materials and Methods: Group 1 – control rats received water ad libitum, Group 2 – HFD group received corn oil orally at a dose of 10mL/kg, Group 3 (HFD+ Atorvastatin (ATV) 10mg/kg), Group 4 (HFD+TA125 mg/kg), and Group 5 (HFD+TA250 mg/kg) were treated as indicated 6 days a week for 5 consecutive weeks. Serum lipid profile and LCAT enzyme activity were evaluated followed by antioxidant parameters and histopathological assessment of heart tissue. Results: HFD group showed elevated levels of lipid profile and alterations in antioxidant parameters, LCAT enzyme activity and histology of heart as compared with control group. Administration of standard drug Atorvastatin (10mg/kg), aqueous bark extract of T. arjuna (125 and 250 mg/kg) to HFD group protected the biochemical alterations, LCAT enzyme activity and pathological damage caused to heart tissue. Conclusion: The study findings reveal the protective role of T. arjuna on HFD induced biochemical and cardiovascular changes implicating antioxidant and therapeutic potential.
Keywords: Terminalia arjuna; Histopathology; Atorvastatin; Lipid profile; LCAT enzyme; Rats